How would the Rogun Dam affect water and energy scarcity in Central Asia? - Bekchanov, Maksud; Ringler, Claudia; Bhaduri, Anik; Jeuland, M. (Informa UK Limited, 2015)
The construction of the Rogun Dam in the Amu Darya Basin to increase upstream energy generation creates potential trade-offs with existing downstream irrigation, due to the different timing of energy and irrigation water demands. The present analysis, based on a hydro-economic optimization model, shows that cooperative basin-wide maximization of benefits would lead to large increases in upstream hydropower production and only minor changes in downstream irrigation benefits. However, if upstream stations, including Rogun, are managed unilaterally to maximize energy production, hydropower benefits might more than double while irrigation benefits greatly decrease, thereby substantially reducing overall basin benefits.